2018
DOI: 10.1080/19411243.2018.1512067
|View full text |Cite
|
Sign up to set email alerts
|

Keyboarding instruction: Comparison of techniques for improved keyboarding skills in elementary students

Abstract: Using computers and keyboarding skills for written communication have been common adaptations recommended by occupational therapists which are now important for all students. We used a quasi-experimental, pre-test/post-test design to examine the effectiveness of a developmentally based curriculum, Keyboarding Without Tears®, as compared to free web-based activities for learning keyboarding skills in students (general and special education) in grades kindergarten through fifth. Overall, students learning the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 17 publications
0
5
0
2
Order By: Relevance
“…Finally, previous studies have also shown that teaching students to touch-type may improve their typing performance, and especially their speed (Donica et al, 2018;Weigelt-Marom & Weintraub, 2015). However, these studies did not systematically examine the students' typing technique, nor the correlation between students' use of fingers and gaze and their typing performance.…”
Section: Study Rationale and Goalsmentioning
confidence: 97%
“…Finally, previous studies have also shown that teaching students to touch-type may improve their typing performance, and especially their speed (Donica et al, 2018;Weigelt-Marom & Weintraub, 2015). However, these studies did not systematically examine the students' typing technique, nor the correlation between students' use of fingers and gaze and their typing performance.…”
Section: Study Rationale and Goalsmentioning
confidence: 97%
“…Adanya aktivitas yang dilakukan oleh siswa dapat menjadi proses berharga dalam diri siswa untuk mencapai skor atau nilai yang diinginkan. Sehingga partisipasi atau aktivitas siswa dalam kegiatan pembelajaran akan berdampak pada retensi materi yang dipelajari serta mampu menumbuhkan kompetensi dan perkembangan pengetahuan [5].…”
Section: Kajian Teori Metode Pembelajaran Drill Dan Aktivitas Siswaunclassified
“…In addition, when investigating again three months after the end of the program, the results showed that speed improved significantly in both groups when compared with preliminary testing. Donica et al [13] evaluated the influence of lecture on keyboard inputting for students (general and special education) in grades kindergarten through fifth.…”
Section: Related Workmentioning
confidence: 99%